Disney It's A Small World: Christmas Around the World - Glass, Calliope (Disney Press, 2012)
Join Pedro, Zanele, and all their friends for some Christmas merriment around the globe. Watch holiday fireworks in Brazil, decorate a mango tree in South Africa, and set out wooden shoes for Sinterklaas in the Netherlands! Filled with holiday cheer, this 8x8 has simple and engaging text, complemented by adorable illustrations inspired by the famous Disney theme parks attraction, It's A Small World!
Keywords: Christmas & Advent; Holidays & Celebrations; Juvenile Fiction